Employers' selection behavior during short-time work - Theresa Scholz (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2012)
During the recession of 2008-09 Germany experienced a huge decrease in GDP. Employment, however, remained surprisingly stable. The so-called German labor market miracle is often ascribed to the intensive usage of short-time work. Despite the resurgence of this instrument, little is known about the employees affected by it. This paper analyzes whether employers select certain individuals for short-time work, where special focus is given on the effect of human capital. The analysis is based on a unique linked-employer-employee data set on short-time workers in the district of the employment agency of Nuremberg. We use methods of event history analysis to estimate transition rates from regular employment to short-time work. Our results indicate that employers select a broad range of workers for STW, irrespective of their level of human capital. Fears that short-time work is mainly applied to a certain group of workers are not confirmed. – – Während der Rezession der Jahre 2008 und 2009 sank das BIP in Deutschland stark.Nichtsdestotrotz blieb das Beschäftigungsniveau überraschend stabil. Das sogenannte deutsche Arbeitsmarktwunder wird oft auf die intensive Nutzung von Kurzarbeit zurückgeführt. Trotz des Wiederauflebens dieses Instruments, ist über die von Kurzarbeit betroffenen Beschäftigten wenig bekannt. Diese Studie analysiert, ob Arbeitgeber bestimmte Personen für Kurzarbeit auswählen, wobei der Einfluss des Humankapitals im Vordergrund steht. Die Analyse stützt sich auf einen einzigartigen linked-employer-employee Datensatz zu Kurzarbeitern im Arbeitsagenturbezirk Nürnberg. Unter Verwendung von Methoden der Ereignisanalyse werden Übergangsraten aus regulärer Beschäftigung in Kurzarbeit geschätzt. Unsere Ergebnisse zeigen, dass Arbeitgeber ein breites Spektrum an Arbeitnehmern für Kurzarbeit auswählen, unabhängig von deren Humankapital. Befürchtungen, dass Kurzarbeit hauptsächlich auf eine bestimmte Gruppe von Arbeitnehmern angewendet wird, werden nicht bestätigt.
Keywords: J23; J24; J3; 330; short-time work; individual data; event history analysis; Unterbeschäftigung; Personalauswahl; Humankapital; Deutschland